PARADIGMA DAN PENDEKATAN PEMIKIRAN MUNAWIR SYADZALI TENTANG STUDI ISLAM - Abdul Basith (LPPM Institut Agama Islam Al-Hikmah Tuban, 2016)
Many thinkers Indonesia who had been instrumental in changing the tradition of thought intlektual in Indonesia in this modern era, among them Harun Nasution, Nur Kholis Majid, Shafi'i Maarif, KH. Abdur Rahman Wahid, KH. MA. Sahal Mahfudh, and so forth, of the range that is Munawir Syadzali, where he through his works has been trying to sell the idea of re-actualization of the teachings of Islam and the concept of the State according to Islam in accordance with the social and cultural conditions in Indonesia, his services in the formation of Madrasah Aliyah Special Program (MAPK), sending lecturers IAIN to study in Western countries, a brilliant idea and breakthrough courageous munawir syadzali can be regarded as a solution to the rigidity of Islamic thought and system of Islamic Education, During his time as Minister of Religion, not a policy that has been taken Munawir Syadzali, of which there are three prominent agenda, first, completing Pancasila social organizations and the fundamental pillars of national life, secondly, the improvement of educational institutions, third, strengthening the presence of the Religious Court and Compilation of Islamic Law.